One Solution to the Urban Crisis: Manly Sports and Winnipeggers, 1900-1914 - Mott, Morris (Urban History Review / Revue d'histoire urbaine, 1983)
In the first decade and a half of the twentieth century, a large number of Winnipeggers became concerned about urban problems in their city. In the opinion of many respected citizens, greater participation in "manly" sports was one method of neutralizing the detrimental physical and moral effects of living in a congested urban environment. The work of these citizens created an explosion of sporting activity in Manitoba's capital during these years. This explosion had a permanent effect on Winnipeg's sporting culture. It bequethed a legacy of innovative promotion and wide community participation, and a sense that sports played by young people should be organized "properly."